Design, synthesis, and biological evaluation of 3,3′-diindolylmethane N-linked glycoconjugate as a leishmanial topoisomerase IB inhibitor with reduced cytotoxicity - Kour P.; Saha P.; Bhattacharya S.; Kumari D.; Debnath A.; Roy A.; Sharma D.K.; Mukherjee D.; Singh K. (My University, 2025)
Leishmaniasis, one of the neglected diseases, ranks second to malaria in the cause of parasitic mortality and morbidity. The present chemotherapeutic regimen faces the limitations of drug resistance and toxicity concerns, raising a great need to develop new chemotherapeutic leads that are orally administrable, potent, non-toxic, and cost-effective. Several research groups came forward to fill this therapeutic gap with new classes of active compounds against leishmaniasis, one such being 3,3′-diindolylmethane (DIM) derivatives. We tried to link this concept with another promising approach of glycoconjugation to study how glycosylated groups work differently from non-glycosylated ones. In the present study, a series of 3,3′-DIM derivatives have been synthesized and screened for their anti-leishmanial potency on Leishmania donovani promastigotes. Next, we synthesized the β-N,N′ glycoside of potent compound 3d using indole-indoline conversion, Fischer-type glycosylation, 2,3-dichloro-5,6-dicyano-1,4-benzoquionone (DDQ) oxidation, and molecular iodine catalyzed coupling with a suitable aldehyde in reasonable overall yield. The biological evaluation revealed that glycosides had reduced cytotoxic effects on the J774A.1 macrophage cell line. The enzyme inhibition study confirms that the glycoside derivatives have significant inhibitory activity against the leishmanial topoisomerase IB enzyme. Molecular docking further displayed the better binding efficiency of glycoside 13 with the target enzyme, suggesting the involvement of more H-bond interactions in the case of glycosides as compared to free drugs. Therefore, this work helps in proposing the fact that the addition of sugar moieties adds some favorable characteristics to free inhibitors, making it a promising approach for future clinical diagnostic and therapeutic applications, which can prove to be a valuable arsenal in combating such neglected diseases. © 2023 RSC.